2008
DOI: 10.1186/1476-7120-6-50
|View full text |Cite
|
Sign up to set email alerts
|

Persistent left superior vena cava: a case report and review of literature

Abstract: Persistent left superior vena cava is rare but important congenital vascular anomaly. It results when the left superior cardinal vein caudal to the innominate vein fails to regress. It is most commonly observed in isolation but can be associated with other cardiovascular abnormalities including atrial septal defect, bicuspid aortic valve, coarctation of aorta, coronary sinus ostial atresia, and cor triatriatum. The presence of PLSVC can render access to the right side of heart challenging via the left subclavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
243
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(261 citation statements)
references
References 7 publications
3
243
1
6
Order By: Relevance
“…Previous reports have shown that a PLSVC may pose difficulties not only in performing central venous catheterization or intracardiac electrode placement, 6) but also in conducting thoracic surgery. 7) However, surgery for treatment of thymic tumors in patients with a PLSVC has not been previously reported; this is the first such case report.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that a PLSVC may pose difficulties not only in performing central venous catheterization or intracardiac electrode placement, 6) but also in conducting thoracic surgery. 7) However, surgery for treatment of thymic tumors in patients with a PLSVC has not been previously reported; this is the first such case report.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, 2 symmetrical cardinal veins (right and left) form the main venous drainage system of the embryo. as another anatomical variant of the venous drainage [7]. PLSVC most frequently coexists with a normal RSVC, the distal part of the RSVC rarely regresses, which means that the PLSVC drains the caudal parts.…”
Section: Discussionmentioning
confidence: 99%
“…In 80-90% of individuals, PLSVC drains into the right atrium directly or via the coronary sinus and is of no hemodynamic consequence. In the remaining cases, it may drain into the left atrium, resulting in a right to left sided shunt (1)(2)(3)(4). Almost 40% of patients with PLSVC have a variety of associated cardiac anomalies, such as atrial septal defects, bicuspid aortic valve, coarctation of the aorta, coronary sinus ostial atresia and cor triatrium (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent left superior vena cava (PLSVC) is the most common thoracic venous anomaly (1). PLSVC is present in 0.3-0.5% of the general population (2,3).…”
Section: Introductionmentioning
confidence: 99%